A qualitative comparison between lecture based and instructional video method of teaching (a follow-up study) - Nicasio Jr., Rene J.; Sia, May Carol Macapia (Adviser).
In a study conducted by J. Fandiaian and P. Lopez in 1997, videocassette recordings have proven its capability as an alternative teaching method. This study aimed to determine which is more effective, instructional video or lecture based method of teaching in terms of long term memory recall. Twenty-four students who participated in the first study were regrouped and asked to answer the same set of questionnaires given to them two years ago. Factors that could have affected the results were identified. With significance level of 0.05, all main factors and their possible interactions were tested and analyzed. The results showed that the method of teaching was the only significant factor that affected the memory recall of the students. The video group had a mean score of 10.38, a 11% increase from the pre-test score of 9.23 and a decrease of 62% from the post-test 1 (13.38). While the lecture group had a mean score of 11.01, an 8% increase from the pre-test score of 11 and a decrease of 49% from the post-test 1 (12.77). The lecture group retained 51% of their memory of the topic while the video group retained 28%. The findings show that lecture method of teaching is more effective in terms of long term memory recall.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.